Tourism Development Strategy in Mangrove Forest of Kampung Sejahtera, Bengkulu City - Sari, Devi Nur Indah; Nyoto Santoso; Rachmad Hermawan (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
The Mangrove Forest of Kampung Sejahtera in Bengkulu City has a strategic location and abundant resources that can be developed into an alternative natural tourist destination. However, this area is not without threats. Therefore, a tourism development strategy should be formulated, taking into account the potential tourism resources and the perceptions of visitors and the local community. Mangrove vegetation data is obtained through field observations using the plot line method at five observation stations, which is then processed to obtain the Importance Value Index and Species Diversity Index Data on wildlife and aquatic biota is obtained through exploration and interviews with fishermen and local communities, as well as the management of Baai Fish Auction Places, Next, the list of types is tabulated by group. Perceptions of tourism development were obtained from visitors and the public with a total of 60 respondents, then processed to obtain the Respondent Achievement Level based on Likert scale values. Based on current management conditions, the potential of flora and leaves, as well as the perceptions of visitors and the community, a tourism development strategy formulation is formulated using a SWOT Analysis. Tourism development strategies can be carried out through strengthening the capacity of community-based tourism management institutions, collaborating with investors to address funding, managing tourism resources and appropriate visitors, creating innovative and educational tourism programs, developing environmental hazard management, creating innovative and environmentally friendly infrastructure, and promoting marketing and advertising through various media, as well as environmental education and law enforcement.